FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KONSUMSI TABLET TAMBAH DARAH PADA IBU NIFAS DI WILAYAH KERJA PUSKESMAS MUTIARA BARAT TAHUN 2019 - Fatmini, Fatmini; Santoso, Heru; Manurung, Kesaktian; Rosdiana, Rosdiana (Universitas Tarumanagara, 2020)
Anemia is still a problem in the world, especially in developing countries. This condition can have a detrimental impact on every age group including pregnant women. In pregnant women, anemia can cause complications for the mother and the baby she is carrying, such as life-threatening bleeding, miscarriage, low birth weight and premature birth. The purpose of this study was to determine the relationship between parity, anemia, ANC visits, nutritional status and the role of health workers with the consumption of blood-added tablets in post-partum mothers in the work area of the Mutiara Barat Health Center in 2019. This type of research is a correlation analytic study with cross-sectional method. The population in this study were all pregnant women in the third trimester who were recorded at the Mutiara Barat Health Center in January 2019 as many as 139 people and the sample was the total population of 139 respondents. Data were analyzed using the chi square statistical test which includes univariate, bivariate and multivariate analysis. The results obtained: there is a relationship between parity (p = 0.000), anemia (p = 0.016), ANC visits (p = 0.015), nutritional status (p = 0.021) and the role of officers (p = 0.000) with the consumption of tablets with blood added at postpartum mother. The dominant factor related to the consumption of blood-added tablets is the role of the officer. From the research results obtained, it is hoped that the Puskesmas can increase the knowledge of mothers about blood supplemented tablets through counseling so that it can influence the attitude of pregnant women to consume blood supplemented tablets. Keywords: ANC visit; anemia; consumption of blood added tablets; nutritional status; parity; role of officers ABSTRAKAnemia masih menjadi permasalahan di dunia terutama di negara-negara berkembang. Kondisi ini dapat memberikan dampak merugikan di setiap kelompok umur termasuk ibu hamil. Pada ibu hamil, kejadian anemia dapat menyebabkan penyulit pada ibu maupun bayi yang dikandungnya seperti perdarahan yang mengancam jiwa, keguguran, berat badan bayi lahir rendah dan kelahiran prematur. Tujuan dari penelitian ini adalah untuk mengetahui hubungan faktor paritas, anemia, kunjugan ANC, status gizi dan peran petugas kesehatan dengankonsumsi tablet tambah darah pada ibu nifas di wilayah kerja Puskesmas Mutiara Barat tahun 2019. Jenis penelitian ini adalah penelitian analitik korelasi dengan metode cross sectional. Populasi dalam penelitian ini adalah seluruh ibu hamil trimester III yang terdata di Puskesmas Mutiara Barat pada bulan Januari 2019 sebanyak 139 orang dan sampel merupakan total populasi yaitu 139 responden. Data dianalisis menggunakan uji statistik chi square yang meliputi analisis univariat, bivariat dan multivariat. Hasil penelitian diperoleh: ada hubungan antara paritas (p=0,000), anemia (p=0,016), kunjungan ANC (p=0,015), status gizi (p=0,021) dan peran petugas(p=0,000) dengan konsumsi tablet tambah darah pada ibu nifas. Faktor yang dominan berhubungan dengan konsumsi tablet tambah darah adalah peran petugas. Dari hasil penelitian yang diperoleh diharapkan Puskesmas dapat meningkatkan pengetahuan ibu tentang tablet tambah darah melalui penyuluhan sehingga dapat mempengaruhi sikap para ibu hamil untuk berperilaku mengkonsumsi tablet tambah darah.